External Efforts to Increase Cocoa Exports to the European Market: A Comparison between Ghana and Indonesia - Satrio, Refin; Kurniawan, Andi (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Cocoa is one of the essential commodities that contribute significantly to the Indonesian economy. As the third largest cocoa-producing country in the world, Indonesia is facing competition from Ghana, a global cocoa-producing country which is relatively similar to Indonesia in terms of politics, economy, and the cocoa industry. Ghana has a competitive advantage that makes its cocoa products appear superior to Indonesia in terms of quality, productivity figures, and cocoa export value. Especially, this is seen in terms of cocoa export to the European Union market. This article aims to study the external efforts made by Ghana and Indonesia to increase their cocoa exports to the European Union market, the largest chocolate consumer region in the world. To do this, it used a qualitative research method with descriptive-analytical and comparative analysis employing the theory of competitive advantage and the concept of economic diplomacy. The article found that Indonesia has excellent cocoa potential that can be developed further and can learn from what Ghana has attempted to increase its cocoa exports to the European Union market.